Measurements and analysis of selected air pollutants in Kuala Lumpur, Kajang and Universiti Pertanian Malaysia - with emphasis on suspended particulate matter - Zainal Abidin, Azman (1987)
Continuous monitoring o f air pollutants in Malaysia was, until recently, virtually non-existent. The installation of three micro-computer system for air monitoring (MCSAM) units , each in Kuala Lumpur, Kajang and Universiti Pertanian Malaysia (UPM),had made it possible to monitor selected air pollutants continuously. From the data acquired from these monitoring systems, several observations were noted. Suspended particulate matter (SPM), oxides of nitrogen (NOx) , carbon monoxide (CO) and, to a small extent, sulphur dioxide (S02) , showed two distinct peaks i n their diurnal patterns. These peaks were evident in the morning hours and late evenings.Diurnal patterns of nitric oxide (NO), nitrogen dioxide (N02) and ozone (03) were "normal", with nitric oxide reaching its peak first,followed by nitrogen dioxide, and finally by ozone several hours later. While these diurnal patterns differed slightly by the locations, they exhibited remarkable similarity by the seasons (namely, the northeast monsoon, the southwest monsoon, and the two transitional seasons). Al though there appeared to be no clear seasonal variations for oxides of nitrogen and ozone, carbon monoxide, on the other hand, remained fairly unchanged throughout the months. Suspended particulate matter, however, showed a distinct peak sometime in the middle of the year. The prolonged dry spell, the formation of strong ground based inversions, and the accompanying local meteorology, were believed to have accounted for the high particulate levels. From the frequency distribution analysis, carbon monoxide and oxides of nitrogen were consistently higher than the corresponding weekday levels of observed to be weekend/holiday levels. For suspended particulate matter , however , there were no noticeable differences b e tween weekday and weekend/holiday levels,due,in part,to the longer residence time of the particulates in the air. Additional analysis on suspended particulate matter was also carried out,using different instruments.